Prospective evaluation of echocardiographic parameters and cardiac biomarkers in healthy dogs eating four custom-formulated diets - Leach, Stacey B.; Clark, Stephanie D.; Baumwart, Ryan D.; McCauley, Sydney R.; Thomason, Justin D.; Streeter, Renee M.; Zumbaugh, Charles A.; Lamb, Ken; Quest, Bradley W. (Frontiers in Animal Science, 2023)
Introduction Diet-associated dilated cardiomyopathy (DCM) has been suspected in breeds that have not been previously noted to have a predisposition to the DCM phenotype. This study hypothesized that over 210 days, dogs fed diets with varying amounts of animal-sourced protein and carbohydrate sources would not be negatively impacted in terms of their cardiac parameters and function. Methods Thirty-two purebred beagles and 33 mixed-breed hounds were randomized into four diet groups and studied for 210 days. The diet groups were as follows: the high-animal-protein grain-free (HAGF) group, the low-animal-protein grain-free (LAGF) group, the high-animal-protein grain-inclusive (HAGI), and the low-animal-protein grain-inclusive (LAGI) group. Cardiac-specific biomarkers, endomyocardial biopsies, and linear and volumetric echocardiographic parameters were evaluated. Results There was a treatment-by-day-by-breed effect observed for the normalized left ventricular internal diameter at end-diastole (p = 0.0387) and for the normalized left ventricular internal diameter at end-systole (p = 0.0178). On day 210, mixed-breed hounds fed the LAGI diet had a smaller normalized left ventricular internal diameter at end-diastole than on day 90. On day 210, beagles fed the LAGF diet had a larger normalized left ventricular internal diameter at end-systole than those fed the LAGI diet. Fractional shortening for beagles in the LAGF group was significantly lower (p = 0.007) than for those in the HAGI and LAGI groups. Cardiac-specific biomarkers and endomyocardial biopsies were not significantly different between breeds, diets, and various time points. Discussion This study did not detect the development of cardiac dysfunction throughout the study period through the echocardiographic parameters measured, select cardiac biomarkers, or endomyocardial biopsies. There were noted interactions of treatment, breed, and time; therefore, isolating a diet association was not possible. Future research should further investigate the other factors that may help to identify the variable(s) and possible mechanisms underlying suspected diet-associated DCM in dogs.